Water Reservoir Placement Methodology for Forest Firefighting: A Case Study of Valparaíso, Chile - Alfaro-Marchant, M; Ternero-Saavedra, R; Santander-Tapia, P; Vargas-Guzman, M; Fuertes-Sanchez, G (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Climate change has a significant impact on generating forest fires. These fires damage property, interrupt productive processes, reduce employment sources, and generate direct economic losses. Also, fires contribute to climate change, resulting in a negative cycle. Therefore, the effective management of forest fires is of vital importance. This research focuses on the combat and mitigation phase of forest fires, with special emphasis on using helicopters to transport water from nearby reservoirs to the fire site. The location of these reservoirs is key since a greater distance traveled by helicopter means a longer delay in water transport, which favors the spread of the fire. For this reason, this research proposes an optimization model to determine the optimal location of these reservoirs in a territory. The proposed model is illustrated with a case study of the region of Valparaiso, demonstrating its usefulness for management and decision making when locating reservoirs for firefighting. © 2024 by the authors.